Sustainable Liquid Biofuels (Bioethanol, Biodiesel) Production and Their Multifunctional Impacts - Oláh, Judit; Popp, József (Journal of Central European Green Innovation, 2022)
The share of fossil energy (oil, coal, natural gas) in final energy consumption was 79.7% in 2019, renewable energy 18.1% and nuclear energy 2.2% worldwide. Renewable energy is the world’s fourth largest source of energy after oil, coal and natural gas, of which "modern" renewables account for 10.6% (wind, solar, hydro, geothermal, biofuels, etc.); traditinal biomass represents 7.5%. Including traditional and modern renewable uses of biomass, bioenergy has contributed 12.7% to the global energy supply. The global spread of biofuel production has provoked serious debate, especially on environmental and social sustainability issues such as its impact on food production, land use change, biodiversity, energy efficiency and climate change. The complexity of economic, social and environmental problems asumes a holistic perspective to reap the benefits of the potential synergy effect. The sustainability of biofuels is, in fact, about optimization between the economic, social and environmental dimensions.